The different distance of the start in swimming - Jeki Haryanto; Naluri Denay (Global Econedu, 2020)
This study aims to determine the difference in the distance start between the racing start and grab start technique. The research design is expost facto research. The population of the research are 23 people, out of these population, the sample was purposive sampling about 12 male swims athletes. To measure the distance of grab start technique and racing start technique then measured using meter tool. To test the research hypothesis, the data analysis technique used is comparative analysis by using the test equation of different mean or t test. Result of research: There is a significant difference between the launch distance of grab start technique with the launch distance in racing start technique. The average launch distance of grab start technique is 9. 26 meters while the average start from racing start technique is 9.04 meters. Thus, the grab start technique is better than racing start technique.